2016
DOI: 10.1002/aelm.201600097
|View full text |Cite
|
Sign up to set email alerts
|

Injection Length in Staggered Organic Thin Film Transistors: Assessment and Implications for Device Downscaling

Abstract: of organic semiconductors show carrier mobility in excess of 5 cm 2 V −1 s −1 when employed as active materials in long (>10 μm) channel organic thin fi lm transistors (OTFT). [2][3][4][5][6][7][8][9][10][11][12] Therefore by scaling the channel length down to 10-1 μm, in principle OTFTs should be able to operate at relatively high (1-10 MHz) frequencies at reasonable (<10 V) applied voltages. [ 13 ] In practice, apart from some reports, [13][14][15][16][17][18][19][20][21][22] this is often not easy to achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 43 publications
2
23
0
Order By: Relevance
“…Depending on the relative values of R C and R ch , the effective injection area can become smaller, with the regions of the electrodes closer to the channel injecting more charges, a phenomena referred to as current crowding . In addition, as L ov is decreased, the contact resistance increases . Ante et al found that R C increased by an order of magnitude when L ov is smaller than the carrier transfer length (the length near the contact through which 63% of charge is transferred), as compared to when L ov is much larger than the carrier transfer length .…”
Section: Charge Injection Through a Metal–semiconductor Interfacementioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the relative values of R C and R ch , the effective injection area can become smaller, with the regions of the electrodes closer to the channel injecting more charges, a phenomena referred to as current crowding . In addition, as L ov is decreased, the contact resistance increases . Ante et al found that R C increased by an order of magnitude when L ov is smaller than the carrier transfer length (the length near the contact through which 63% of charge is transferred), as compared to when L ov is much larger than the carrier transfer length .…”
Section: Charge Injection Through a Metal–semiconductor Interfacementioning
confidence: 99%
“…To achieve high operational speeds, the length of the overlap between the gate and drain/source contacts L ov , shown in Figures c and c, needs to be minimized to reduce the capacitance of the contact. While this would increase device speed, in staggered geometries Natali et al found that there is a minimum contact length to allow for enough area such that there is sufficient current to operate the device . Assuming that the mobility is isotropic, in order to achieve R C ≤ 10% of R tot they suggested that L ov should be 1.5 times larger than the injection length (or transfer length), and that L should be 18 times larger …”
Section: Charge Injection Through a Metal–semiconductor Interfacementioning
confidence: 99%
“…The former component originates from charge injection at the metal‐semiconductor interface and is mainly governed by the Schottky barrier (see Figure a) . The latter component arises from the access transport through the OSC bulk with relatively low charge concentrations and perhaps with an inferior charge transport profile (e.g., caused by contact defects) . Together, these resistances alter the device characteristics, making mobility extraction unreliable or even impossible.…”
Section: Contact Effectsmentioning
confidence: 99%
“…dual--gate or encapsulated top--gate field--effect transistor devices) [28,29]. Moreover, the typical deposition techniques used for fabricating multilayer PhCs such as Pulse Laser Deposition and Atomic Layer Deposition enable the deposition of high density oxides on top of soft material such as organic and inorganic thin--films [30]. Finally, the realization of the BP--based photonic systems is also compatible with the deposition of BP by means of liquid exfoliation assisted by sonication [31].…”
Section: Resultsmentioning
confidence: 99%